Factors influencing repeated teenage pregnancy: a review and meta-analysis - Maravilla, J.; Betts, K.; Couto e Cruz, C.; Alati, Rosa (Mosby, Inc., 2017)
© 2017 Elsevier Inc. Objective: Existing evidence of predictors of repeated teenage pregnancy has not been assessed rigorously. This systematic review provides a comprehensive evaluation of protective and risk factors that are associated with repeated teenage pregnancy through a metaanalytical consensus. Data Sources: We used PubMed, EMBASE, CINAHL, ProQuest, PsychINFO, ScienceDirect, Scopus, and Web of Science databases from 1997–2015 and the reference list of other relevant research papers and related reviews. Study Eligibility Criteria: Eligibility criteria included (1) epidemiologic studies that analyzed factors associated with repeated pregnancy or birth among adolescents <20 years of age who were nulliparous or experienced at least 1 pregnancy, and (2) experimental studies with an observational component that was adjusted for the intervention. Study Appraisal and Synthesis Methods: We performed narrative synthesis of study characteristics, participant characteristics, study results, and quality assessment. We also conducted random-effects and quality-effects metaanalyses with meta-regression to obtain pooled odds ratios of identified factors and to determine sources of between-study heterogeneity. Results: Twenty-six eligible epidemiologic studies, most from the United States (n=24), showed >47 factors with no evidence of publication bias for each metaanalysis. Use of contraception (pooled odds ratio, 0.60; 95% confidence interval, 0.35–1.02), particularly long-acting reversible contraceptives (pooled odds ratio, 0.19; 95% confidence interval, 0.08–0.45), considerably reduced repeated teenage pregnancy risk. Among studies about contraception, the number of follow-up visits (adjusted coefficient, 0.72; P=.102) and country of study (unadjusted coefficient, 2.57; permuted P=.071) explained between-study heterogeneity. Education-related factors, which included higher level of education (pooled odds ratio, 0.74; 95% confidence interval, 0.60–0.91) and school continuation (pooled odds ratio, 0.53; 95% confidence interval, 0.33–0.84), were found to be protective. Conversely, depression (pooled odds ratio, 1.46; 95% confidence interval, 1.14–1.87), history of abortion (pooled odds ratio, 1.66; 95% confidence interval, 1.08–2.54), and relationship factors, such as partner support, increased the repeated teenage pregnancy risk. Conclusion: Contraceptive use, educational factors, depression, and a history of abortion are the highly influential predictors of repeated teenage pregnancy. However, there is a lack of epidemiologic studies in low- and middle-income countries to measure the extent and characteristics of repeated teenage pregnancy across more varied settings.